Nitrogen Balance after the Administration of a Prolonged-Release Protein Substitute for Phenylketonuria as a Single Dose in Healthy Volunteers - Scheinin Mika; Junnila Jouni; Reiner Giorgio; MacDonald Anita; Muntau Ania C. (MDPI, 2022)
Nitrogen balance is the difference between nitrogen excreted as urea and nitrogen ingested, mainly in proteins. Increased circulating concentrations of amino acids (AA) in the bloodstream are usually associated with proportional increases in the production and excretion of urea. Previously, we reported results from a randomized, controlled, single-dose, crossover trial in healthy adult volunteers (n = 30) (Trial Registration: ISRCTN11016729), in which a Test product (prolonged-release AA mixture formulated with Physiomimic Technology (TM) (PT (TM))) significantly slowed down the release and reduced the peak plasma concentrations of essential AAs compared with a free AA mixture (Reference product) while maintaining essential AA bioavailability. Here, we report an assessment of the nitrogen balance from the same study. The amount of nitrogen contained in plasma AAs, levels of blood urea nitrogen (BUN) (p < 0.0001) and changes in BUN (p < 0.0001) were smaller after the Test product compared with the Reference product. These findings suggest that the production of urea in proportion to systemic AA availability was significantly smaller after the administration of the Test product compared with the Reference product and that the test product conferred the increased utilization of AAs for protein synthesis and reduced their oxidation and conversion to urea. In the clinical setting, it is possible that the effects of PT (TM) observed on the disposition of free AAs in this study may translate to health benefits in terms of physiological body composition and growth if used for the treatment of subjects with phenylketonuria (PKU). Further investigation in patients with PKU is warranted.